Assortative mating by colored ornaments in blue tits: space and time matter. Issue 7 (26th February 2017) - Fargevieille, Amélie; Grégoire, Arnaud; Charmantier, Anne; del Rey Granado, Maria; Doutrelant, Claire
Abstract: Assortative mating is a potential outcome of sexual selection, and estimating its level is important to better understand local adaptation and underlying trait evolution. However, assortative mating studies frequently base their conclusions on small numbers of individuals sampled over short periods of time and limited spatial scales even though spatiotemporal variation is common. Here, we characterized assortative mating patterns over 10 years in four populations of the blue tit ( Cyanistes caeruleus ), a passerine bird. We focused on two plumage ornaments—the blue crown and the yellow breast patch. Based on data for 1, 657 pairs of birds, we found large interannual variation: assortative mating varied from positive to negative. To determine whether there was nonetheless a general trend in the data, we ran a within‐study meta‐analysis. It revealed that assortative mating was moderately positive for both ornaments. It also showed that mating patterns differed among populations and especially between two neighboring populations that displayed phenotypic divergence. Our results therefore underscore that long‐term studies are needed to draw broad conclusions about mating patterns in natural populations. They also call for studying the potential role of assortative mating in local adaptation and evolution of ornaments in both sexes. Abstract : Assortative mating studies frequently base their conclusions on small numbers of individuals sampled over short periods of time and limited spatial scales even though spatiotemporal variation is common. Based on 10 successive years of color measurements in four populations of blue tits ( Cyanistes caeruleus ), a meta‐analytic approach revealed moderately positive assortative mating on two ornaments in the four populations beyond major temporal variation. We also discovered variation among populations. Overall these findings suggest assortative mating may play a role in the evolution of ornaments in both sexes, and it underscores the necessity to use long‐term studies to draw solid conclusions about mating patterns in natural populations.